Prevalence and global trends of polypharmacy among people living with HIV: a systematic review and meta-analysis - Mohammed I. Danjuma; Oyelola A. Adegboye; Ahmed Aboughalia; Nada Soliman; Ruba Almishal; Haseeb Abdul; Mohamad Faisal Hamad Mohamed; Mohamed Nabil Elshafie; Abdulatif AlKhal; Abdelnaser Elzouki; Arwa Al-Saud; Mas Chaponda; et al. (SAGE Publishing, 2022)
Background: There has been a rising prevalence of polypharmacy among people living with HIV (PLWH). Uncertainty however remains regarding the exact estimates of polypharmacy among these cohorts of patients. Methods: We conducted a systematic search of PubMed; EMBASE, CROI, Cochrane Database of Systematic Reviews; Science Citation Index and Database of Abstracts of Reviews of Effects for studies between 1 January 2000 and 30 June 2021 that reported on the prevalence of polypharmacy (ingestion of > 5 non-ART medications) among PLWH on antiretroviral therapy regimen (ART). Prevalence of polypharmacy among HIV-positive patients on ART with Clopper-Pearson 95% confidence intervals were presented. The heterogeneity between studies was evaluated using I 2 and τ 2 statistics. Results: One hundred ninety-seven studies were initially identified, 23 met the inclusion criteria enrolling 55,988 PLWH, of which 76.7% [95% confidence interval (CI): 76.4-77.1] were male. The overall pooled prevalence of polypharmacy among PLWH was 33% (95% CI: 25-42%) ( I 2  = 100%, τ 2  = 0.9170, p  < 0.0001). Prevalence of polypharmacy is higher in the Americas (44%, 95% CI: 27-63%) ( I 2  = 100%, τ 2  = 1.0886, p  < 0.01) than Europe (29%, 95% CI: 20-40%) ( I 2  = 100%, τ 2  = 0.7944, p  < 0.01). Conclusion: The pooled prevalence estimates from this synthesis established that polypharmacy is a significant and rising problem among PLWH. The exact interventions that are likely to significantly mitigate its effect remain uncertain and will need exploration by future prospective and systematic studies. Registration: PROSPERO: CRD42020170071 Plain Language Summary Background: In people living with HIV (PLWH), what is the prevalence of polypharmacy and is this influenced by sociodemographic factors? Methods and Results: In this systematic review and meta-analysis of 23 studies comprising 55,988 participants, we have for the first time found an estimated polypharmacy pooled prevalence of 33% among PLWH. There was a relatively higher pooled prevalence of polypharmacy among the America's compared with European cohorts of PLWH. Conclusion: Polypharmacy among PLWH is a rising morbidity that needs urgent intervention both at policy and patient levels of care.